An Empirical Analysis of the Decision-Making Style of Millennials on the Choice of Financial Products - N.Mahalakshmi, T; Munuswamy, Shanmugam (Indian Journal of Marketing, 2022)
Purpose : The millennial generation was brought up in the digital age, so they were expected to have a different decision-making style than their previous generation. Understanding their psychology was vital for the financial services sector to segment them and develop efficient marketing strategies. Hence, this study aimed to determine the impact of investment decision-making styles on the choice of stock investments among millennial investors in India. Design/Methodology/Approach : A structured questionnaire was adopted to collect responses from millennial investors through snowball sampling. The validity and reliability of the data were tested. Further, the measurement and structural models were analyzed using partial least squares SEM with the help of Smart PLS 3.0 to observe the impact of investor decision-making styles on the choice of stock investments. Findings : Confused by over-choice, impulsiveness, and novelty consciousness styles were found to have a significant positive relationship, whereas brand loyalty and hedonism had a negative impact on the choice of stock investments among millennial investors. Research Limitations/Implications : The study was conducted among millennial investors. Therefore, future research can focus on other generations as independent or comparative studies to get more insights. Originality/Value : To the best of our knowledge, our study is the first to explore the decision-making style of millennial investors in the context of stock market investments with specific reference to emerging markets.